Study on the influence of uneven settlement and small curve radius on metro train running safety and riding comfort. (May 2023) - Zhang, Jinfeng; Zhu, Zixu; Zhu, Xueyan; Meng, Yichen; Chu, Weihong
Abstract: Shield tunnels are susceptible to large uneven settlements owing to their low longitudinal stiffnesses, which can lead to structural defects and unfavorable wheel–rail interactions. These conditions may even worsen if uneven settlement occurs in curved track sections with small radii. Therefore, the running safety and riding comfort of metro trains should be considered when dealing with curved tunnel sections with differential settlements. In this study, a train–curved-track–tunnel dynamic interaction model was established to evaluate the influence of uneven settlement and a small curve radius on the running safety and riding comfort of a metro train under different curve radii, vehicle speeds, and settlement ranges and amplitudes. Considering initial random irregularities with respect to the longitudinal level and alignment, the dynamic responses of the vehicle were determined, including the wheel–rail forces, accelerations of the vehicle, wheel load reduction rate, derailment coefficient, and stability index. In addition, the characteristics of uneven settlement when the vehicle responses reached peak values were illustrated. The results revealed that the wheel–rail lateral and vertical forces increased significantly with an increase in velocity. The wheel load reduction rate, derailment coefficient, and lateral comfort were negatively correlated with the curve radius, whereas vertical comfort was not very sensitive to changes in the curve radius. Additionally, the outer wheel exhibited a greater load reduction than the inner wheel, thus leading to a greater likelihood of derailment. More attention should therefore be directed toward the settlement wavelengths and amplitudes at which the wheel load reduction rate, derailment coefficient, and vertical and lateral riding comfort indexes achieve their maximum values.